THE RELATIONSHIP OF KNOWLEDGE, ATTITUDE, AND PERCEPTION OF HIV/AIDS PATIENTS TO TRANSMISSION PREVENTION - aziz, ari rahmat (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2023)
ABSTRACTHuman Immunodeficiency Virus (HIV) / AIDS infection was increased every year. One of the causes of new sufferers is the risky sexual behavior people with HIV / AIDS. The purposed of this study is to analyze the Determinant of risk prevention behavior of transmission people with HIV / AIDS in Arifin Achmad Public Hospital. The research method used cross-sectional study to describe the determinant of prevention of transmission of HIV / AIDS. The research sample was 83 respondents. The study was conducted from Jun 2, 2021 to July 2, 2021 in Arifin Achmad Public Hospital. The results showed that of 83 respondents, 26 (31%) respondents had risky behavior and 57 (68%) respondents had healthy behavior. Analyze with statistics showed there are not correlation between Knowledge (p value = 0.119) with prevention of transmission HIV AIDS patient. There are correlation between attitude (0.015), perception (0.009) with prevention of transmission HIV/ AIDS. These results encourage care giver to be more active in providing health education. Keywords: Sexual behavior; HIV/ AIDS Patient;